A qualitative understanding of the effects of reusable sanitary pads and puberty education: implications for future research and practice - Julie Hennegan; Catherine Dolan; Laurel Steinfield; Paul Montgomery (BMC, 2017)
Abstract Background The management of menstruation has come to the fore as a barrier to girls' education attainment in low income contexts. Interventions have been proposed and piloted, but the emerging nature of the field means limited evidence is available to understand their pathways of effect. Methods This study describes and compares schoolgirls' experiences of menstruation in rural Uganda at the conclusion of a controlled trial of puberty education and sanitary pad provision to elucidate pathways of effect in the interventions. Semi-structured interviews were undertaken with schoolgirls who participated in the Menstruation and the Cycle of Poverty trial concurrent with the final set of quantitative surveys. A framework approach and cross-case analysis were employed to describe and compare the experiences of 27 menstruating girls across the four intervention conditions; education (n = 8), reusable sanitary pads (n = 8), education with reusable sanitary pads (n = 6), and control (n = 5). Results Themes included: menstrual hygiene, soiling, irritation and infection, physical experience, knowledge of menstruation, psychological, social and cultural factors, and support from others. Those receiving reusable pads experienced improvements in comfort and reliability. This translated into reduced fears around garment soiling and related school absenteeism. Other menstrual hygiene challenges of washing, drying and privacy remained prominent. Puberty education improved girls' confidence to discuss menstruation and prompted additional support from teachers and peers. Conclusions Findings have important implications for the development and evaluation of future interventions. Results suggest the provision of menstrual absorbents addresses one core barrier to menstrual health, but that interventions addressing broader needs such as privacy may improve effectiveness. Puberty education sessions should increase attention to body awareness and include strategies to address a wider range of practical menstrual challenges, including pain management. Interviews revealed possibilities for improving quantitative surveys in future research. Trial registration Pan-African Clinical Trials Registry PACTR201503001044408